Colour Doppler ultrasound after major cardiac surgery improves diagnostic accuracy of the pulmonary infection score in acute respiratory failure: A prospective observational study. Issue 9 (September 2019) - Dureau, Pauline; Bouglé, Adrien; Melac, Audrey Tanguy; Ait Hamou, Nora; Arbelot, Charlotte; Ben Hassen, Kais; Charfeddine, Ahmed; Deransy, Romain; Arcile, Gauthier; Rouby, Jean-Jacques; Granger, Benjamin; Amour, Julien
Abstract : BACKGROUND: Postoperative pneumonia is a frequent complication after cardiac surgery, and its diagnosis is difficult. Little is known about the diagnostic accuracy of lung ultrasound (LUS) in the detection of pneumonia in cardiac surgical patients. The substitution of chest radiography by colour Doppler LUS (LUS-sCPIS) in the simplified clinical pulmonary infection score (sCPIS) could improve the diagnosis of pneumonia following cardiac surgery. OBJECTIVE: The aim of this study was to compare the diagnostic accuracy of LUS-sCPIS and of sCPIS alone in the detection of postoperative pneumonia after cardiac surgery. DESIGN: A prospective study of diagnostic accuracy. SETTING: A Surgical Intensive Care Unit of a French University Hospital. PATIENTS: Fifty-one patients with acute respiratory failure within 72 h after cardiac surgery were enrolled between January and May 2015. MAIN OUTCOME MEASURE: The two index tests, LUS-sCPIS and sCPIS, were calculated for all patients at the onset of acute respiratory failure. The reference standard for the diagnosis of pneumonia was based on the consensus of three physicians, blind to the sCPIS and LUS-sCPIS data, based on a posthoc review of all the clinical, radiological and microbiological evidence. The diagnostic accuracy of LUS-sCPIS was compared with that of sCPIS in the detection of postoperative pneumonia. RESULTS: Pneumonia was diagnosed in 26 out of 51 patients. The LUS-sCPIS detected the presence of pneumonia with a sensitivity of 92% (95% CI 0.85 to 0.99) and a specificity of 68% (95% CI 0.55 to 0.81). The sCPIS detected the presence of pneumonia with a sensitivity of 35% (95% CI 0.22 to 0.48) and a specificity of 84% (95% CI 0.74 to 0.94). The area under the curve (AUC) of LUS-sCPIS at 0.80 (95% CI 0.69 to 0.91) was higher than the AUC of sCPIS at 0.59 (95% CI 0.47 to 0.71; P = 0.0008). CONCLUSION: Compared with sCPIS, LUS-sCPIS improved diagnostic accuracy in the detection of postoperative pneumonia in patients with acute respiratory failure after cardiac surgery. It could be a useful bedside tool to guide pneumonia management. TRIAL REGISTRATION: Clinicaltrials.gov identifier: NCT03279887. Abstract : Supplemental Digital Content is available in the text